UNMODIFIED AND GOLD-MODIFIED SEMICONDUCTOR CATALYSTS FOR SOLAR LIGHT ASSISTED PHOTODEGRADATION OF CRYSTAL VIOLET - PAPP, Zsigmond (Studia Universitatis Babeș-Bolyai Chemia, 2017)
Different unmodified and modified semiconductor photocatalysts were used for the complete decolorization of an unbuffered crystal violet solution. The decolorization efficiency of commercially available ZnO and TiO2 (anatase nanopowder) was compared with those of newly prepared gold-modified ZnOs (Au/ZnOs). Two Au/ZnOs were prepared from pure ZnO powder through deposition of gold by direct current (DC) sputtering. The morphological characterization of the Au/ZnOs was done with the aid of scanning electron microscopy. ZnO-based catalysts show significantly higher decolorization power in comparison with TiO2. Au/ZnOs show slightly higher activity than unmodified ZnO.